Cellular, molecular and genomic alterations in the hatchlings of Labeo rohita after exposure to Triclosan - Sharma, Sunil; Dar, Owias Iqbal; Andotra, Megha; Sharma, Simran; Bhagat, Ankeet; Thakur, Sharad; Kesavan, Anup Kumar; Kaur, Arvinder (Frontiers in Environmental Science, 2022)
To obtain biomarkers for the acute stress of TCS (commonly used antibacterial agent) hatchlings of Labeo rohita were exposed for 96h to 0.06, 0.067 and 0.097 mg/L TCS. Morphological deformities, cell viability, frequency of micronucleated and aberrant cells, transcriptomic and biomolecular alterations were recorded after exposure and a depuration period of 10 days. The exposed hatchlings had pointed head, curved trunk, lean body, deformed caudal fin, haemorrhage, hypopigmentation and tissue degeneration at 0.067 and 0.097 mg/L only. The frequency of viable cells declined but that of necrotic, apoptotic, micronucleated and abnormal cells increased (p ≤ 0.01) in a concentration dependent manner after exposure as well as the depuration period. Compared to 96h values, the viable and micronucleated cell frequency increased but the frequency of necrotic, apoptotic and aberrant cells decreased after recovery. The mRNA level of HSP47, HSP70, HSc71 and α- tropomyosin increased (p ≤ 0.01), while that of HSP60, HSP90, DHPR, myosin light polypeptide 3, desmin b and lamin b1 declined (p ≤ 0.01) after exposure. 10 days post exposure, a significant increase (p ≤ 0.01) over control was observed in the expression of all the heat shock and cytoskeletal genes and the values (except for HSc71) were higher than the respective 96h values also. Infrared spectra showed that band area of amide A, amide I, amide II and phospholipids increased significantly (p ≤ 0.01) but peak intensity of lipid, glycogen and nucleic acids decreased after exposure. After recovery, area of the peaks for most of the biomolecules [except lipids (2924-2925, 1455-1457 cm-1) and glycogen (1163-1165 cm-1)] declined significantly over control and 96h values. It is evident that HSP60, HSc71, HSP90, α- tropomyosin and DHPR were strongly affected but DHPR can be used as the most sensitive marker for the toxicity of TCS.